2019
DOI: 10.1016/j.chembiol.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Conformational Energy Landscape of CDK1 and CDK2 Suggest a Mechanism for Achieving Selective CDK Inhibition

Abstract: SummaryDysregulation of the cell cycle characterizes many cancer subtypes, providing a rationale for developing cyclin-dependent kinase (CDK) inhibitors. Potent CDK2 inhibitors might target certain cancers in which CCNE1 is amplified. However, current CDK2 inhibitors also inhibit CDK1, generating a toxicity liability. We have used biophysical measurements and X-ray crystallography to investigate the ATP-competitive inhibitor binding properties of cyclin-free and cyclin-bound CDK1 and CDK2. We show that these k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 66 publications
(110 reference statements)
1
89
0
Order By: Relevance
“…Many studies have suggested that CDK2 could be a crucial factor in the progression of cancer by regulating several pathways and might be a prospective biomarker and indicator of prognosis. Therefore, CDK2 and its cyclin binding partners are possible therapeutic targets for future cancer treatments (Yin et al, 2018;Zhang et al, 2018;Wood et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that CDK2 could be a crucial factor in the progression of cancer by regulating several pathways and might be a prospective biomarker and indicator of prognosis. Therefore, CDK2 and its cyclin binding partners are possible therapeutic targets for future cancer treatments (Yin et al, 2018;Zhang et al, 2018;Wood et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The 3D-models of protein kinases were constructed with the Swiss-Model web-service [18]. The structural model of plant cyclin-dependent kinase 1 (CDKA1_ARATH, UniProtKB: P24100) was constructed using RCSB ProteinDataBank tamplate structure 6gu7 (X-Ray diffraction, 2.75 Е) of human cyclin-dependent kinase 1 [19]. The structural model of plant Cdk 1 from S. cerevisiae (CDK1_YEAST, UniProtKB: P00546) was also constructed using structure 6gu7 [19].…”
Section: Methodsmentioning
confidence: 99%
“…The structural model of plant cyclin-dependent kinase 1 (CDKA1_ARATH, UniProtKB: P24100) was constructed using RCSB ProteinDataBank tamplate structure 6gu7 (X-Ray diffraction, 2.75 Е) of human cyclin-dependent kinase 1 [19]. The structural model of plant Cdk 1 from S. cerevisiae (CDK1_YEAST, UniProtKB: P00546) was also constructed using structure 6gu7 [19]. The structural model of YAK1-related kinase (UniProtKB: Q8RWH3) from A. thaliana was taken from our previous research [20].…”
Section: Methodsmentioning
confidence: 99%
“…This dimeric scaffold is initiative for the design of other derivatives with a significant activity against CDKs as reported 8 , 9 . Other isatin derivatives decorated with 3-substitution expressed potent inhibition for CDK2 as shown in SU9516 which inhibits CDK2 with IC 50 = 25 nM ( Figure 1 ) 10 . Moreover, compound ( I ) is another isatin derivative with hydrazino linker at position 3 (CDK2; IC 50 = 60 nM) that was co-crystallized with its target and submitted to protein data bank (1VFT).…”
Section: Introductionmentioning
confidence: 99%